Past malaria epidemics in Sri Lanka - an analysis - Punsiri Fernando (Journal of the College of Community Physicians, 2014)
DOI: http://dx.doi.org/10.4038/jccpsl.v19i1.7624 Journal of the College of Community Physicians of Sri Lanka Vol.19(1) December 2013 27-41